2011
DOI: 10.1093/ndt/gfr479
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular fluid volume and glomerular filtration rate in 1878 healthy potential renal transplant donors: effects of age, gender, obesity and scaling

Abstract: There are several significant differences in GFR and ECV between healthy men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 29 publications
4
55
1
1
Order By: Relevance
“…The mean GFR of 107 ml/min/1.73 m 2 was first suggested by original data obtained by Piepsz et al [29,30] ferent from 107 ml/min/1.73 m 2 but this difference is clearly not relevant from a clinical point of view, as the mean mGFR was 104.9 ml/min/1.73 m 2 . Moreover, the study by Peters et al [15] has the largest impact (weight) on the meta-analysis results, since this is the study with the largest number of subjects, but at the same time, this study consistently showed the lowest mean mGFR values for all age groups. Without the Peters data, the mean mGFR in the 30-40 years age group becomes 105.6 with a 95% CI of 103.4-107.8, which includes 107.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The mean GFR of 107 ml/min/1.73 m 2 was first suggested by original data obtained by Piepsz et al [29,30] ferent from 107 ml/min/1.73 m 2 but this difference is clearly not relevant from a clinical point of view, as the mean mGFR was 104.9 ml/min/1.73 m 2 . Moreover, the study by Peters et al [15] has the largest impact (weight) on the meta-analysis results, since this is the study with the largest number of subjects, but at the same time, this study consistently showed the lowest mean mGFR values for all age groups. Without the Peters data, the mean mGFR in the 30-40 years age group becomes 105.6 with a 95% CI of 103.4-107.8, which includes 107.…”
Section: Discussionmentioning
confidence: 69%
“…In the age groups 20-30, 30-40, 50-60 and 60-70 years, the largest influence was obtained from the study of Peters et al [15] , with a significant decrease in heterogeneity I 2 when omitted. In the age group of 40-50 years, the study of Poggio et al [9] showed the largest influence, and when omitted, heterogeneity I 2 = 90.3% decreased to 82.2%.…”
Section: Sensitivity Analysismentioning
confidence: 95%
“…In one study, healthy men and women of the same SA had similar levels of GFR (29), although in another study GFR/SA was slightly (4.5%) higher in men than in women. Still, GFR scaled to SA between men and women is more similar than GFR scaled to V (29,30). For this reason, it has been suggested that V-based dialysis dosing be rescaled to SAN-stdKt/V (6).…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding median values in the current prospective renal transplant donors were both 0.18 l/kg [11].…”
Section: Resultsmentioning
confidence: 83%
“…There has been much discussion recently about the shortcomings of BSA for physiological scaling, especially in children in whom the BSA is relatively large in relation to body mass and gives a value of scaled GFR that is significantly lower in relation to the rate constant of the terminal exponential of the plasma clearance curve (α 2 ) [6]. Moreover, it is interesting to note that values of mECV in healthy adult donors when scaled to BSA were 13.0 and 12.0 l/1.73 m 2 [11], respectively, which are much higher than those in children (see Table 1) and the reverse of the difference between adults and children seen with scaling to weight. The equation of Bird et al (Eq.…”
Section: Discussionmentioning
confidence: 99%